Tinjauan Criteria Supplier-Selection, Integrasi Internal dan Eksternal Supply Chain terhadap Kinerja Perusahaan - Anjar Wibisono (BISMA (Bisnis dan Manajemen), 2018)
Performance measurement reflects the company capability to prepare the customer desired standard when in time it considers lower production and maintenance costs, higher product quality, reduced stock in process, deprived material processing cost, and shorter delivery deadline. The key to improve company performance locates at integrated effectiveness building, internally or externally, through cooperation and coordination begun with supplier-selection criteria between business partners. Supply Chain Management (SCM) requires: internal integration (intra-organization) and external integration (inter-organization). Primary key of Supply Chain Management (SCM) will be having supplier as partner in the company strategy and satisfying the always changing market demand. Therefore, a selection among company strategy options in the global competition really produces a model of dominant integration, coordination, and cooperation in controlling global market, precisely through supply chain as important element to contribute to company performance improvement.